Comparative effect of ultrasound-assisted extraction configuration method on the physicochemical characteristics of tuna skin gelatin - IMRAN MUHTAR; SYAHRIATI SYAHRIATI; RAHMAWATI SALEH; ILHAM AHMAD; SITTI RAMLAH; ROSNIATI ROSNIATI; JUSTUS ELISA LOPPIES (Smujo International, 2026)
Abstract. Muhtar I, Syahriati, Saleh R, Ahmad I, Ramlah S, Rosniati, Loppies JE. 2026. Comparative effect of ultrasound-assisted extraction configuration method on the physicochemical characteristics of tuna skin gelatin. Asian J Agric 10 (1): g100129. https://doi.org/10.13057/asianjagric/g100129. Gelatin is a biopolymer widely used in the food industry. The main challenge lies in the low yield and quality of gelatin produced through conventional extraction methods. This study aims to enhance the efficiency and quality of tuna (Thunnus albacares) skin gelatin by employing various extraction configurations. Tuna skin obtained from industrial processing by-products is then cleaned, cut uniformly, weighed, and used for pre-treatment and extraction. Tuna skin samples were obtained from processing by-products at PT. Nirvana Niaga Sejahtera from Indonesia in 2025. The extraction methods used include Water Bath Extraction (WBE), Ultrasound-Assisted Extraction Pre-Alkali-Acetic Treatment (UAE-PRAA), and Ultrasound-Assisted Extraction Post-Acetic Treatment (UAE-PSAA). The UAE process was carried out at 175 W power, 25 kHz frequency, and 55°C for 60 minutes. The parameters analyzed included yield, composition (protein, moisture, and ash contents), pH, viscosity, gel strength, and structural characteristics, as determined by Fourier Transform Infrared (FTIR). The results showed that the UAE-PSAA method produced the highest yield (13.34±0.22%), significantly (p<0.05) greater than UAE-PRAA (6.60±0.15%) and WBE (5.01±0.12%). The highest protein content was found in WBE (81.39±0.02 g/100g) and UAE-PSAA (80.44±0.28 g/100g), while the lowest moisture content was observed in UAE-PSAA (5.16±0.17 g/100g), indicating better drying efficiency. The lowest ash content (0.62±0.02 g/100g) was also obtained from UAE-PSAA, reflecting higher extraction purity. Gel strength (164.32±0.04 g) and viscosity (10.00±0.05 cP) significantly (p<0.05) improved with the UAE-PSAA method. FTIR analysis revealed minor spectral shifts toward lower wavenumbers in the amide regions, indicating molecular rearrangements that improved the functional properties of the extracted gelatin. Overall, the UAE-PSAA configuration significantly (p<0.001) enhances yield, physicochemical quality, and molecular stability of tuna skin gelatin, demonstrating strong potential for scalable and sustainable industrial applications.